2021
DOI: 10.1093/mnras/stab1306
|View full text |Cite
|
Sign up to set email alerts
|

A highly accreting low-mass black hole hidden in the dust: Suzaku and NuSTAR observations of the NLS1 Mrk 1239

Abstract: We present torus modelling for the X-ray spectra of a nearby narrow-line Seyfert 1 galaxy Mrk 1239 (z = 0.0199), based on archival Suzaku, NuSTAR and Swift observations. Our model suggests very soft intrinsic power-law continuum emission of Γ ≈ 2.57 in 2019 and Γ ≈ 2.98 in 2007. By applying a correction factor to the unabsorbed X-ray luminosity, we find that Mrk 1239 is accreting near or around the Eddington limit. Our best-fit spectral model also suggests a torus with a column density of log (NH, ave/ cm−2) =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…We used the spectra from all three XIS detectors for the simultaneous fitting in the energy range 0.5-10 keV of all four observations. We removed the energy bins between 1.7 and 2.3 keV to avoid the calibration uncertainties due to the artificial structures around Si and Au edges (Jiang et al 2021).…”
Section: Xis Spectramentioning
confidence: 99%
“…We used the spectra from all three XIS detectors for the simultaneous fitting in the energy range 0.5-10 keV of all four observations. We removed the energy bins between 1.7 and 2.3 keV to avoid the calibration uncertainties due to the artificial structures around Si and Au edges (Jiang et al 2021).…”
Section: Xis Spectramentioning
confidence: 99%
“…Typically, the photon index is linked to the photon index of the primary continuum (power law). There is no evidence of a power law below 2 keV; thus, Γ was fixed to Γ = 2.5, a typical value of the photon index found in Mrk 1239 (Buhariwalla et al 2020;Jiang et al 2021). The iron abundance was fixed to solar abundance.…”
Section: The Low-energy Spectrum Below 2 Kevmentioning
confidence: 99%
“…They did not detect the O triplet located at ∼ 0.56 keV leading them to conclude that there was an overabundance of Ne in Mrk 1239. Subsequent works have used this overabundance while fitting the X-ray spectra (see Jiang et al 2021). The analysis of Buhariwalla et al (2020) suggested the excess emission at 0.91 keV was in fact due to a blend of emission lines including the Ne triplet and Fe-L emission lines.…”
Section: Neon Abundancementioning
confidence: 99%
“…As for Mrk 1239 this does not seem to be the case as no matter the number of photoionized components applied (in addition to powerlaw components) the spectra is still under fit between 13 − 17 Å without the addition of . Mrk 1239 is a polar scattered Seyfert 1 galaxy, meaning our line of sight (LOS) passes through the upper layers of the torus polarizing the optical emission (Smith et al 2004;Jiang et al 2021). ESO 323-G77, another polar scattered Seyfert1, presents an X-ray spectra similar to Mrk 1239.…”
Section: Mrk 1239 Compared To Seyfert Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation